Concomitant Juvenile Myasthenia Gravis and Polymyositis in a Child: A Case Report - Castro, Ana Costa e (2021)
Acute muscle weakness is a major neurological emergency with a vast differential diagnosis. Even though inflammatory myopathies and myasthenia gravis are rare causes of acute muscle weakness, especially in children, there have been descriptions of coexistence of both diseases in adults, especially in association with thymoma. We report a case of a pediatric patient with concurrent MG and IM and comment on relevant features and difficulty in diagnosing both diseases.